The Impact of Interval Training and Leg Muscle on The Endurance Capacity of Football Players (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to assess the impact of lengthy and rigorous interval training methods on aerobic and anaerobic endurance by analyzing leg muscle endurance capabilities. The study employed a quasi-experimental design using a pretest-posttest methodology without a control group, involving 24 athletes under the age of 14, divided into 4 groups. The evaluation instruments utilized were the Balke test for aerobic endurance and the Running-Based Anaerobic Test (RAST) for anaerobic endurance. The studies conducted were the t-test and the ANOVA test. The study's findings revealed that T-test analysis showed a substantial effect on both aerobic and anaerobic endurance, with significance values of p=0.000 for extended training and p=0.000 for intensive interval training. The ANOVA test revealed no significant differences among the training methods, leg muscle endurance levels, or their interaction, as all significance values surpassed 0.005 (p>0.005). Both extensive and demanding interval training enhance anaerobic and aerobic endurance, with no significant distinction between the two approaches.  Moreover, variations in leg muscle capacity influence both aerobic and anaerobic endurance; yet, there is no notable difference or interaction between the interval training method and the degree of leg muscular endurance.